I'll pay you later: Sustaining relationships under the threat of expropriation - Elena Paltseva; Gerhard Toews; Marta Troya-Martinez (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2022)
Contracts between governments and international firms are difficult to enforce, especially under weak institutions: governments are tempted to renegotiate tax payments after investments occurred. Theoretically, such a hold-up problem is solved by using selfenforcing agreements that increase the value of sustaining the relationship over time. By delaying production, tax payments and investments, firm's threat to terminate following a renegotiation becomes more effective. Using rich proprietary data on the oil and gas industry, we show that contracts between the oil majors and petro-rich economies with weak institutions are indeed delayed relative to countries with strong institutions. To push for a causal interpretation, we show that this backloading in countries with weak institutions only emerges in early 1970s. We attribute this to a change in the international view towards countries' sovereignty over natural resources brought by the poswar weakning of the OECD countries. This new world order made it politically difficult for developed countries to continue the established practice of military interventions to back up the enforcement of the contracts of their oil firms. Fading of (military) enforcement, together with the absence of local legal enforcement, triggered the need to backload the contracts.
Keywords: D86; L14; O13; H20; P48; Q30; 330; Dynamic Incentives; Political Economy; Institutions; Oil